Journal Review: Analysis and Validation Using HPLC in the Analysis of Nonsteroidal Anti-Inflammatory Drugs - Allya Luthfi Artikasari; Ayika Elvarreta Amanta; Arzeti Shabila Tri Hapsari; M. Rodiatul Iman; Hata Rianti Wasahua; Naira Parsa; Fauzia Aisyah Tsabita; Kanaya Shabrina Maharani (INDOGENIUS, 2026)
Background & Objective: Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) are widely used to treat inflammation and pain by inhibiting the cyclooxygenase enzyme, which reduces prostaglandin synthesis. High-Performance Liquid Chromatography (HPLC) is an analytical technique widely applied for the determination of NSAIDs because it is capable of separating organic, inorganic, biological, and non-volatile compounds with high precision.  Method: This study presents a literature review of 24 national and international publications obtained from Google Scholar, ScienceDirect, and PubMed. The reviewed articles were evaluated based on HPLC instrumental parameters and validation, including the type of chromatographic column, mobile phase composition, flow rate, injection volume, detection wavelength, retention time, recovery, limit of detection (LOD), and limit of quantification (LOQ). The method used was a literature review with a descriptive-qualitative approach. Result: The review results showed that all studies reported good analytical performance, with linearity values of r ≥ 0.99, recovery percentages in the range of 98–102%, and precision values with %RSD < 2%. LOD and LOQ values varied across studies, but all fell within the acceptable range according to the ICH Q2(R1) validation guidelines. Conclusion: These findings provide a comprehensive overview of the optimal chromatographic conditions for the analysis of various NSAID formulations using the HPLC method, and confirm that HPLC is an accurate, precise, and sensitive technique for determining NSAID concentrations.